Pengaruh Terpaan Iklan Dan Brand Loyalty Terhadap Minat Beli Produk Samsung Galaxy - Yoganata, Dionisius Aditya (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2019)
The purpose of this research is to find out whether exposure to advertising and brand loyalty influences buying interest of Samsung Galaxy products. The theory used in this study is the AIDA model (Attention, Interest, Desire, Action), and the Advertising Exposure Process proposed by David. A Aaker. The research method used by the authors in this study is a quantitative method approach. The objects in this study are those who want to make purchases of Samsung Galaxy products, as well as those who have already used Samsung Galaxy products, which are determined by 85 respondents of the study sample. This research is quantitative descriptive, where the primary data collected through questionnaires are processed statistically, so that the measurement scale. The results of this study indicate that the variable exposure to advertising has an influence on buying interest of Samsung Galaxy by 46.6 percent. Also, the brand variable variable has an influence on buying interest of Samsung Galaxy products by 48.4 percent. Also, the variable exposure to advertising and brand loyalty has an influence on buying interest of Samsung Galaxy products by 61.8 percent together. Meanwhile, the rest is influenced by other variables not examined in this study. The conclusion of this study shows that there is an influence between exposure to advertising and brand loyalty on the purchase interest of Samsung Galaxy products, both partially and simultaneously. Suggestions from this study that the author can provide include further research of a similar nature in order to use other variables not contained in this study. Also, it is hoped that this research can be used as a reference, both for producers and those who should be consumers.